33rd AIAA Applied Aerodynamics Conference 2015
DOI: 10.2514/6.2015-3159
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stall Prediction for Swept Wings Using Low-Order Aerodynamics

Abstract: The ability of low-order aerodynamic prediction methods, such as the vortex lattice method, to predict the force and moment characteristics of arbitrary wing geometries, including those with sweep, is well established for pre-stall conditions. Approaches to augment such methods by modeling the flow separation as an effective reduction in camber has allowed extension of the predictive capability to stall and post-stall conditions for unswept wings. Such approaches assume locally two-dimensional flow and use air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The lift curves of the set of wings from Hosangadi et al [9] as computed by CFD and the present method are shown in Figure 5a. It may be observed that the present method has the proper sensitivity to the wing sweep.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lift curves of the set of wings from Hosangadi et al [9] as computed by CFD and the present method are shown in Figure 5a. It may be observed that the present method has the proper sensitivity to the wing sweep.…”
Section: Resultsmentioning
confidence: 99%
“…In a finite swept wing, the 2.5D polars vary along the span, having a higher � � at the root than at the tip. This behavior is discussed in a paper by Hosangadi et al [9] using the CFD results from [10]. We propose a method for modelling the 2.5D polars of finite wings based on assigning an effective (i.e.…”
Section: Aerodynamic Polars: 2d To 25dmentioning
confidence: 98%
See 1 more Smart Citation